Análisis de Nivel Sub-Nacional de Política de Desarrollo de Biotecnología en Brasil: Innovación Tecnológica y la Salud Humana en el Estado de Bahía - Daniela Caffé de Oliveira; Ilka Biondi (Journal of Technology Management & Innovation, 2013)
The potential of biotechnology for research and development (R & D) in various areas of knowledge is reflected in actions for the promotion of technological innovation in Brazil from the demands of productive sectors and health. Considering the Brazilian scenario regarding the weaknesses and strengths of the Health Industrial Complex (HIC), the aim of this study was to analyze the current stage of implementation of the National Biotechnology Development Policy (PDB) in the State of Bahia, in the sector of human health, considering the structural actions - (i) investments, (ii) human resources, (iii) infrastructure. Through an exploratory descriptive study were identified developments, in particular the existence of programs “Bahia Inovação” and “Empreende Bahia” that stimulates entrepreneurship and technological innovation. However, in spite of the existing scientific and technological capacity in the state, there are few projects submitted and funded in the field of biotechnology.